KADAR BRIX BERBAGAI RUAS BATANG DAN SIFAT-SIFAT AGRONOMI SORGUM (Sorghum bicolor (L.) Moench) PADA FASE DAUN BENDERA - Solihat, Nur Aenun; Anugrahwati, Dwi Ratna; Zubaidi, Akhmad (Agros Journal of Agriculture Science, 2024)
Sorghum (Sorghum bicolor (L.) Moench) is a potential multipurpose crop to be developed in Indonesia and has a wide adaptation and can grow on all types of soil except on acidic yellow-red soil. The experiment conducted aimed to evaluate the Brix levels and agronomic characters of several sorghum varieties in the flag leaf phase. This experiment was conducted at the Glasshouse of the Faculty of Agriculture, Mataram University from May to September 2023. The design used in this experiment was a completely randomized design (CRD) with variety as a treatment, namely the varieties Gando Bura, Gando Keta, Bioguma, Samurai, Super 1, Super 2, and Suri 4. In this experiment, each treatment was repeated 3 times so that there were 21 experimental units. The parameters observed were plant height, number of leaves, number of tillers, leaf angle, stem diameter, dry matter weight, and Brix content. Observation data were analyzed using Analysis of Variance (ANOVA) at the 5% level. The results showed that the agronomic characters and brix levels of local and national sorghum varieties in the flag leaf phase had significant differences in the parameters of plant height, leaf angle, stem diameter, dry matter weight, and average Brix levels of plant stems. The highest plant height and dry matter weight were found in the Super 2 variety, the largest leaf angle was found in the Suri 4 variety, the largest stem diameter was found in the Suri 4 and Super 2, and the highest brix levels were found in the Super 2, Suri 4, and Gando Keta.